2004
DOI: 10.1590/s0101-81752004000200038
|View full text |Cite
|
Sign up to set email alerts
|

Core area and centre of activity of maned wolves, Chrysocyon brachyurus (Illiger) (Mammalia, Canidae), submitted to supplemental feeding

Abstract: Revista Brasileira de Zoologia 21 (2): 391-395, junho 2004Usually, home ranges comprise heterogeneous areas determined by physical and biological factors, which explain the disproportionate use of space by animals. Studies on various species show that, for a number of environment-related reasons, certain portions within the home range are more frequently used than others

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…During the course of our study a parallel study on the effect of supplemental feeding on the center of activity and the diet of these maned wolves was being undertaken. This study showed that although the wolves did utilize the supplemental food on a daily basis (approximately 30% of their daily intake), they also hunted vertebrate and invertebrate prey and consumed plants [Silva and Talamoni, 2004]. Furthermore, a study of their ecology and habitat selection showed many parameters, such as home range size, to be in accordance with published values for wild maned wolves [see Coelho et al, 2008].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…During the course of our study a parallel study on the effect of supplemental feeding on the center of activity and the diet of these maned wolves was being undertaken. This study showed that although the wolves did utilize the supplemental food on a daily basis (approximately 30% of their daily intake), they also hunted vertebrate and invertebrate prey and consumed plants [Silva and Talamoni, 2004]. Furthermore, a study of their ecology and habitat selection showed many parameters, such as home range size, to be in accordance with published values for wild maned wolves [see Coelho et al, 2008].…”
Section: Discussionsupporting
confidence: 69%
“…It may of course be that the male was performing other important roles necessary for the survival of offspring such as territorial marking. In the parallel study of Silva and Talamoni [2004] the maned wolves deposited many feces close to the sanctuary where the supplemental feeding was taking place. Dietz, based on his studies of wild maned wolves in Brazil (1984Brazil ( , 1985, suggests that individuals place feces to mark their territory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food enhancement can affect animal socioecology (Kanurai , Sapolsky & Share , Silva & Talamoni , Fuentes , Riley et al . ).…”
mentioning
confidence: 99%
“…Food enhancement can affect animal socioecology (Kanurai 2004, Sapolsky & Share 2004, Silva & Talamoni 2004, Fuentes 2006, Riley et al 2011. Food provisioning may alter movement ecology (sensu Nathan 2008) and consequently the spatial and social decisions of animals (Southwick et al 1965, Kawanaka 1973, Lindburg 1977.…”
mentioning
confidence: 99%